Plasma elimination kinetics for factor VII are independent of its activation to factor VIIa and complex formation with plasma inhibitors - Petersen, Lars C.; Elm, Torben; Ezban, Mirella; Krogh, Thomas N.; Karpf, Ditte M.; Steinø, Anne; Olsen, Eva H. N.; Sørensen, Brit B. (Thrombosis and Haemostasis, 2009)
The mechanism for the elimination of factor VII (FVII) from the circulation is unknown, just as it is unclear how activation of FVII to FVIIa and subsequent complex formation with antithrombin III (AT) or α2-macroglobulin (α2M) affects clearance. The possibility that the clearance mechanism involves activation and inhibitor complex formation as obligatory intermediate reactions is examined in this study. Human and murine sera were spiked with human FVIIa in the absence and presence of heparin and analysed for complex formation. Complex formation in vivo was studied after intravenous injection of 125I-VIIa in mice; and the pharmacokinetics (PK) of human and murine FVIIa was studied in normal mice. Furthermore, comparative PK studies were performed with FVII, FVIIa, active site blocked FVIIa and a preformed FVIIa-AT complex in normal and α2M-deficient mice. The data demonstrated that FVIIa-AT complexes and to a much lesser extent FVIIa-α2M-complexes accumulated in vivo after FVIIa administration. FVIIa-AT accounted for about 50% of total FVIIa antigen left in the circulation after 3 hours. All FVII derivatives studied including FVII, FVIIa and FVIIa-AT were cleared with similar rates suggesting an elimination kinetics which is unaffected by FVII activation and subsequent inactivation by plasma inhibitors.
Keywords: Factor VIIa; antithrombin; alpha2-macroglobulin; complex formation; clearance